MSMEs Empowerment Strategy and Traditional Market Arrangement in Serang City: SWOT Analysis of Dinkopukmperindag Serang City - Munjazi, Tubagus (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2024)
This research analyzes strategies for empowering Micro, Small, and Medium Enterprises (MSMEs) and developing traditional markets in Serang City using SWOT analysis. Data shows that Serang City has 10,321 MSMEs, far behind Lebak Regency with 50,338 MSMEs. The SWOT analysis shows that the Office of Cooperatives, Small and Medium Enterprises, Industry and Trade of Serang City (Dinkopukmperindag) has strengths such as training programs for employees and strategic partnerships with various stakeholders. However, there are also weaknesses such as poor trade area management and lack of access to capital for MSMEs. In order to empower MSMEs and develop traditional markets in Serang City, the right strategy is needed to maximize strengths and opportunities and overcome weaknesses and threats. This research is expected to provide strategic recommendations for Dinkopukmperindag Kota Serang in improving the performance and empowerment of MSMEs and maintaining the sustainability of traditional markets as the center of the local economy.